Potential impact and host range of Pereskiophaga brasiliensis Anderson (Curculionidae): a new candidate biological control agent for the control of Pereskia aculeata Miller (Cactaceae) in South Africa - Mdodana, Lumka Anita (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2018)
Pereskia aculeata Miller (Cactaceae) is a damaging invasive alien plant in South Africa that has negative impacts to indigenous biodiversity and ecosystem functioning. Mechanical and chemical control are not effective against P. aculeata so biological control is considered the only viable option. Two biological control agents, the leaf-feeding beetle Phenrica guerini Bechyne (Chrysomelidae) and the stem-wilting bug Catorhintha schaffneri (Coreidae), have been released in South Africa thus far. Post-release evaluations have indicated that P. guerini will not reduce P. aculeata densities to acceptable levels alone, while C. schaffneri was released very recently, so it is too soon to determine how effective that agent will be. Even if C. schaffneri is extremely damaging, it is likely that further agents will be required to reduce the densities of P. aculeata to acceptable levels within a reasonable time-scale. Additional agents should target the woody stems of P. aculeata which are not impacted by the damage of either of the released agents. Pereskiophaga brasiliensis Anderson (Curculionidae) is a promising potential candidate agent that feeds on the thick woody stems of the plant in the larval stage. Climatic matching, genetic matching and field based host specificity observations all indicated that P. brasiliensis was a promising candidate. In this study, the impact of P. brasiliensis to the target weed, P. aculeata, was quantified under quarantine conditions to determine whether it was sufficiently damaging to warrant release. This was followed by host specificity testing to determine whether P. brasiliensis was suitably host specific for release in South Africa. Impact studies indicated that P. brasiliensis was damaging to P. aculeata at insect densities that would be expected in the field. Pereskiophaga brasiliensis reduced the number of leaves of P. aculeata to a greater extent than it reduced shoot lengths, but both plant parameters were significantly reduced due to the feeding damage from the insect. This suggests that the damage from P. brasiliensis may be compatible with that of C. schaffneri which reduces shoot length to a greater degree than the number of leaves. Pereskiophaga brasiliensis is therefore sufficiently damaging to warrant release, and although interaction studies with the other agents would be required, it is expected that it should complement other existing agents. Although P. brasiliensis is sufficiently damaging, at present the host specificity data indicates that it is not suitably specific for release in South Africa because oviposition and larval development to the adult stage was recorded on both indigenous and alien plant species within the families Cactaceae and Basellaceae. This non-target feeding was recorded during no-choice tests, which are very conservative, but significant non-target damage and development to the adult stage was recorded on an indigenous plant from a different family to the target weed. Further host specificity testing, including paired and multiple choice tests, are required to confirm the broad host range of P. brasiliensis. Other biological control agents that damage the woody stems of P. aculeata should be considered. The stem-borer, Acanthodoxus machacalis (Cerambycidae) is considered the most promising of the other candidate agents as it can be sourced from a climatically matched region where genetically suitable P. aculeata plants are found, it is sufficiently damaging to the woody stems of P. aculeata and there is no evidence that the species has a broad host range. Acanthodoxus machacalis should be sourced from Rio de Janeiro, Brazil, and imported into quarantine in South Africa for host specificity testing.
Keywords: Curculionidae -- South Africa; Cactus -- South Africa; Biological pest control agents; Alien plants-- -- South Africa; Pereskiophaga brasiliensis Anderson (Curculionidae); Pereskia aculeata Miller (Cactaceae)